Detection of microorganisms by fluorescence in situ hybridization using peptide nucleic acid - Oliveira, Ricardo (2020)
Fluorescence in situ hybridization (FISH) is a 30-year-old technology that has evolved continuously and is now one of the most well-established molecular biology techniques. Traditionally, DNA probes are used for in situ hybridization. However, synthetic molecules are emerging as very promising alternatives, providing better hybridization performance and making FISH procedures easier and more efficient. In this chapter, we describe a universal FISH protocol, using nucleic acid probes, for the detection of bacteria. This protocol should be easily applied to different microorganisms as a way of identifying in situ relevant microorganisms (including pathogens) and their distribution patterns in different types of samples.